EFFECTIVENESS OF GIVING MORINGA LEAF EXTRACT (MORINGA OLEIFERA) IN REDUCING BLOOD PRESSURE SYSTEMATIC REVIEW - Rifkia, Via; Zahra, Rahmanita Kamila; Kolib, Abdul (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2023)
Hypertension, which is an increase in blood pressure, has a prevalence based on Riskesdas in 2018 at the age ≥18 years, which is around 34.1%. Various treatment methods have been developed because if hypertension is not treated it can cause symptoms and serious complications. Other than using chemical drugs such as beta-blockers or ACE inhibitors, people are starting to consider therapy with natural ingredients such as Moringa leaves (Moringa oleifera). It contains compounds that have an antihypertensive effect such as flavonoids and potassium. This study aims to determine the compound, effectiveness, and mechanism of Moringa leaf as an antihypertensive by using a systematic review method. This method is carried out by searching literature using certain keywords based on PRISMA-P, and then data from ten literatures is extracted to be discussed and concluded based on the objectives. The result, obtained various compounds in Moringa leaf extract have certain mechanisms in lowering blood pressure such as flavonoid compounds, such as kaempferol and quercetin, as well as other compounds such as several organic acids, potassium, and alkaloids. Moringa leaf extract also effectively lowers blood pressure in animals and humans with different doses. This study concludes that the administration of Moringa leaf extract can effectively reduce blood pressure due to the antihypertensive mechanism caused by the phytochemical content.